Cognitive Stimulation and Strength Training in Older Adults with Mild Cognitive Impairment: A Randomized Controlled Trial - Juan Miguel Muñoz-Perete; María del Mar Carcelén-Fraile; Yolanda Castellote-Caballero; María del Carmen Carcelén-Fraile (Diagnostics)
Background/Objectives: The global increase in life expectancy has led to a higher prevalence of cognitive and physical decline in older adults, particularly in those with mild cognitive impairment (MCI). This study aimed to evaluate the effects of a combined cognitive stimulation and resistance training intervention on cognitive performance, physical function, and fall risk in older adults with MCI. Methods: A randomized controlled trial was conducted with 80 community-dwelling older adults diagnosed with MCI. Participants were randomly assigned to an experimental group (EG), which received a 12-week intervention consisting of cognitive stimulation and progressive strength training, or a control group (CG), which maintained their usual routine. Pre- and post-intervention assessments included measures of cognitive function, verbal fluency, attention, processing speed, executive function, gait, balance, fall risk, and lower- and upper-body strength. Results: The EG showed significant improvements compared with the CG in cognitive impairment, verbal fluency, processing speed, balance, gait, and risk of falls (all p < 0.05), with effect sizes ranging from moderate to large. Notably, strength gains were observed in both lower body and grip strength. Attention and executive function also improved in the EG, although with smaller effect sizes. No adverse events were reported. Conclusions: A combined intervention of cognitive stimulation and resistance training is effective in improving multiple domains of cognitive and physical function in older adults with MCI. These findings support the integration of multidomain interventions in clinical and community settings to promote autonomy, reduce fall risk, and delay cognitive and functional decline. Future studies should explore the long-term sustainability of these effects and the individual contribution of each intervention component.